Dietary supplementation effects of Chlorella vulgaris on performances, oxidative stress status and antioxidant enzymes activities of prepubertal New Zealand White rabbits - A. B. Sikiru; A. Arangasamy; I. C. Alemede; S. S. A. Egena; R. Bhatta (Bulletin of the National Research Centre, 2019)
Abstract Background Chlorella vulgaris (CV) is a natural source of functional antioxidants capable of protecting against oxidative stress; its dietary supplementation in animals can serve as a way of improving animals’ performance and productive output; on this background, the microalgae was supplemented to growing New Zealand white rabbits and its effects on performances and oxidative stress status were evaluated. Method Thirty-five (35) 6-week-old New Zealand White rabbits (935.48 ± 5.92 g) were divided into five groups (n = 7 per group) in a completely randomized design experiment; rabbits in control groups were fed only commercial rabbits feed, while rabbits in treatment groups were supplemented with 200, 300, 400, and 500 mg Chlorella vulgaris biomass per kilogram of the body weight along with commercial rabbits feed daily. Feed intake and body weight changes were recorded daily and weekly; at the end of the study, blood was collected and subjected to chemical assays for evaluation of serum oxidative stress markers and antioxidant activities. Results Dietary supplementation of the microalgae significantly increased the rabbits’ growth weights (p < 0.01) without significant increase or reduction in feed intakes (p < 0.56), but significantly enhanced feed to gain ratio. The microalgae supplementation significantly protected the rabbits against oxidative stress damages through the reduction of malondialdehyde concentrations (p < 0.001) and increased total antioxidant capacity (p < 0.003). It also led to higher superoxide dismutase activity (p < 0.001), increased catalase activity (p < 0.003), and higher concentration of reduced glutathione (p < 0.001). Conclusion It was concluded from outcomes of both performance and biochemical analysis of the rabbits that daily supplementation of Chlorella vulgaris between 200 and 500 mg per kilogram of the body weight in prepubertal rabbits significantly improved performances in forms of higher weight gains and enhanced feed utilization; it also protected against oxidative stress damages hence it was recommended as dietary antioxidant supplement for growing prepubertal rabbits.